2020
DOI: 10.1021/acsomega.0c00803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein and Mechanical Strain on the Corrosion Resistance and Cytotoxicity of the Orthodontic Composite Arch Wire

Abstract: In this study, the effects of the exposure to different types of salivary proteins (fibrinogen, IgG, and mucin) and application of an in vitro bending strain on the laser welding orthodontic composite arch wire (CAW) were investigated, and the resultant corrosion behavior and cytotoxicity were studied in vitro. The purpose was to determine the mechanisms by which protein exposure and bending loads contribute to the corrosion of the CAW either alone or in combination by mimicking the clinical application. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Hussain et al [ 42 ] observed that ion release depends more on the type of alloy and the process of its manufacture than on the amount of ions in the alloy. According to He et al, saliva proteins influence the alloys metal ion release and have also an important role in corrosion resistance improvement [ 43 ].…”
Section: Metal Ions Release During Treatment With Fixed Orthodontic Appliancesmentioning
confidence: 99%
“…Hussain et al [ 42 ] observed that ion release depends more on the type of alloy and the process of its manufacture than on the amount of ions in the alloy. According to He et al, saliva proteins influence the alloys metal ion release and have also an important role in corrosion resistance improvement [ 43 ].…”
Section: Metal Ions Release During Treatment With Fixed Orthodontic Appliancesmentioning
confidence: 99%